Current Understanding of the Wettability of MXenes. Issue 2 (9th December 2022) - Yu, LePing; Lu, Lu; Zhou, XiaoHong; Xu, Lyu
Abstract: Since the first report regarding the successful fabrication of few‐layer transition metal carbides (known as MXenes) of 2011, their intrinsic properties, such as mechanical strength and electrical conductivity, are intensively studied. Though the hydrophilic nature of MXenes is widely reported and utilized to fabricate various functional materials, there is a lack of systematic study with respect to the science behind the wetting phenomena of MXene‐based materials. The goal of this manuscript is to provide some useful guidelines in the design of novel MXene‐based systems with desirable wetting properties by analyzing the current understanding of the wettability of MXenes. Specifically, after the introduction of the fundamental concepts in wetting theory, the wettability of pure MXene films is summarized based on the recently published results from both theoretical and experimental studies. Then, the determining factors in the wetting properties of MXenes associated with surface architectures and chemical compositions are clarified, which is followed by the effect of hybridization strategies discussed in detail. In the end, a summary of the abundant applications relying on the wetting properties of MXene‐based systems is presented along with the current challenges and the corresponding future research directions in this field. Abstract : As the wettability of MXenes plays an important role in practical applications, investigating the intrinsic wetting properties of these novel 2D materials is therefore necessary. Herein, the detailed analysis of the results from both theoretical and experimental studies unravels the wetting essence of MXenes and further facilitates the development of strategies for controlling the wettability to deal with industrial challenges.